A Family of Small Coiled-Coil–forming Proteins Functioning at the Late Endosome in Yeast - Kranz, Andreas (The American Society for Cell Biology, 2001)
The multispanning membrane protein Ste6, a member of the ABC-transporter family, is transported to the yeast vacuole for degradation. To identify functions involved in the intracellular trafficking of polytopic membrane proteins, we looked for functions that block Ste6 transport to the vacuole upon overproduction. In our screen, we identified several known vacuolar protein sorting (VPS) genes (SNF7/VPS32, VPS4, and VPS35) and a previously uncharacterized open reading frame, which we named MOS10 (more of Ste6). Sequence analysis showed that Mos10 is a member of a small family of coiled-coil–forming proteins, which includes Snf7 and Vps20. Deletion mutants of all three genes stabilize Ste6 and show a “class E vps phenotype.” Maturation of the vacuolar hydrolase carboxypeptidase Y was affected in the mutants and the endocytic tracer FM4-64 and Ste6 accumulated in a dot or ring-like structure next to the vacuole. Differential centrifugation experiments demonstrated that about half of the hydrophilic proteins Mos10 and Vps20 was membrane associated. The intracellular distribution was further analyzed for Mos10. On sucrose gradients, membrane-associated Mos10 cofractionated with the endosomal t-SNARE Pep12, pointing to an endosomal localization of Mos10. The growth phenotypes of the mutants suggest that the “Snf7-family” members are involved in a cargo-specific event.